Principles of care for acquired hemophilia. (18th March 2021) - Dolan, Gerry; Benson, Gary; Bowyer, Annette; Eichler, Hermann; Hermans, Cedric; Jiménez‐Yuste, Victor; Ljung, Rolf; Pollard, Debra; Santagostino, Elena; Šalek, Silva Zupančić
Abstract: Objective: To establish clear priorities for the care of patients with acquired hemophilia A (AHA) by proposing 10 key principles of practical, holistic AHA management. Method: These principles were developed by the Zürich Haemophilia Forum, an expert panel of European hemophilia specialists comprising physicians and nursing and laboratory specialists. Results: The 10 proposed principles for AHA care are as follows: (a) Improving initial diagnosis of AHA; (b) Differential diagnosis of AHA: laboratory assessment of patients with unusual bleeding; (c) Effective communication between laboratories, physicians, and specialists; (d) Improving clinical care: networking between healthcare professionals in the treating hospital and specialist hemophilia centers; (e) Comprehensive assessment of bleeding; (f) Appropriate use of bypassing agents; (g) Long‐term follow‐up and monitoring for efficacy and safety of immunosuppressive treatment; (h) Inpatient/outpatient settings; (i) Access to innovative and disruptive treatments; (j) Promotion of international collaborative research. Conclusion: The proposed principles for holistic AHA care aim to ensure swift diagnosis and optimal patient management. Key to achieving this goal is training for healthcare personnel in non‐specialist hospitals and collaboration between different specialists. We hope these principles will increase awareness of AHA in the wider medical community and catalyze efforts toward improving its practical, multidisciplinary management.